Potential Impact of Diabetes and Obesity on Alveolar Type 2 (AT2)-Lipofibroblast (LIF) Interactions After COVID-19 Infection - Nouri-Keshtkar, Marjan; Taghizadeh, Sara; Farhadi, Aisan; Ezaddoustdar, Aysan; Vesali, Samira; Hosseini, Roya; Totonchi, Mehdi; Kouhkan, Azam; Chen, Chengshui; Zhang, Jin-San; Bellusci, Saverio; Tahamtani, Yaser (Frontiers in Cell and Developmental Biology, 2021)
SARS-CoV-2, a new emerging respiratory virus, caused evolving pneumonia outbreak around the world. In SARS-Cov-2 infected patients, diabetes mellitus (DM) and obesity are two metabolic diseases associated with higher severity of SARS-CoV-2 related complications, characterized by acute lung injury requiring assisted ventilation as well as fibrosis development in surviving patients. Different factors are potentially responsible for this exacerbated response to SARS-CoV-2 infection. In patients with DM, base-line increase in inflammation and oxidative stress represent preexisting risk factors for virus-induced damages. Such factors are also likely to be found in obese patients. In addition, it has been proposed that massive injury to the alveolar epithelial type 2 (AT2) cells, which express the SARS-CoV-2 receptor angiotensin-converting enzyme 2 (ACE2), leads to the activation of their stromal niches represented by the Lipofibroblasts (LIF). LIF are instrumental in maintaining the self-renewal of AT2 stem cells. LIF have been proposed to transdifferentiate into Myofibroblast (MYF) following injury to AT2 cells, thereby contributing to fibrosis. We hypothesized that LIF’s activity could be impacted by DM or obesity in an age- and gender-dependent manner, rendering them more prone to transition towards the profibrotic MYF status in the context of severe COVID-19 pneumonia. Understanding the cumulative effects of DM and/or obesity in the context of SARS-CoV-2 infection at the cellular level will be crucial for efficient therapeutic solutions.